The Real Tragedy of the Commons – Garrett Hardin (1968) Revised - Brunnhuber, Stefan (Problemy Ekorozwoju, 2022)
Garrett Hardin’s seminal 1968 paper describes the tragedy of the commons in terms of common goods being neglected or overused. His theory has been widely adopted. However, it refers only to a special case, when inadequate public goods have to compete with the maximisation of private yield. The real tragedy of the commons is not that it is overused or neglected, nor is it any free-rider and spillover effects it gives rise to, but rather the underlying financial incentives and disincentives that prevent an adequate supply. Consequently, the misalignment between our current monetary system and the global commons has led to the latter’s erosion and partial destruction. Introducing a new monetary and fiscal policy of strategic triangulation can provide an adequate tool to finance our commons. With their ongoing central bank digital currency (CBDC) initiatives, regulators and central banks can offer a direct monetary mechanism to overcome this tragedy of the commons.